Coated modified ternary positive electrode material as well as preparation method and application thereof
By covering the core surface of the ternary positive electrode material with a sub-oxide layer, a transition layer and a carbon layer, the problem of the high-nickel ternary positive electrode material prone to side reactions under high cutoff voltage is solved, and the high cycle stability, lithium ion capacity and rate performance of the material are improved.
Patent Information
- Application Number
- CN202411921160.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing high-nickel ternary cathode materials are prone to side reactions with the electrolyte at high cutoff voltage, resulting in electrochemical performance loss, and the residual lithium on the electrode surface reacts with water, oxygen and carbon dioxide to form lithium compounds, hindering Li+ migration and affecting the performance stability of the material.
By covering the surface of the ternary positive electrode material core with the silicon oxide layer, the transition layer and the carbon layer, the interaction between the ternary positive electrode material core and the electrolyte is prevented, side reactions are reduced, and lithium ion capacity and electron conductivity are improved.
It effectively improves the cycle stability, lithium ion capacity and rate performance of the coated modified ternary cathode material, and meets the needs of practical applications.
Smart Images

Figure BDA0005208034440000181 
Figure BDA0005208034440000191
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials, and relates to a coated modified ternary positive electrode material, and in particular to a coated modified ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] As an energy storage device that can replace fossil energy, lithium-ion batteries have the advantages of high energy density, long service life and environmental friendliness, and have attracted widespread attention. At present, lithium-ion batteries are widely used in various fields such as portable electronic devices, electric vehicles and microchips. However, with the increasing demand for battery life in electronic devices and electric vehicles, the research on positive electrode materials for batteries with high energy density and low preparation cost is particularly important. High-nickel ternary positive electrode materials have become the first choice for positive electrode materials of lithium-ion batteries due to their high energy density. However, under high cut-off voltage, the electrolyte hydrolysis product HF will react with the high-nickel ternary positive electrode material, resulting in a loss of electrochemical performance; in addition, the residual lithium on the surface of the high-nickel ternary positive electrode material electrode is easy to react with water, oxygen and carbon dioxide to generate lithium compounds on the surface, thereby hindering Li + Migration. These defects are important factors in the performance degradation of high-nickel ternary cathode materials, which seriously restricts the development of high-nickel ternary materials.
[0003] Coating a chemically inert coating on the surface of a high-nickel ternary positive electrode material is considered a promising solution. The above problems can be alleviated to a certain extent by coating the positive electrode material. Commonly used positive electrode coating layers in the prior art mainly include metal oxide coating, lithium compound coating and carbon coating. However, the electronic conductivity and / or lithium ion pass rate of the coating layer disclosed in the prior art is low. While suppressing the side reactions of the high-nickel ternary positive electrode material, it also hinders the rapid deintercalation of lithium ions, resulting in the lithium ion capacity and rate performance of the coated high-nickel ternary positive electrode material failing to meet the needs of practical applications.
[0004] CN106571455A discloses a silver-loaded mesoporous silica-coated ternary positive electrode material and a preparation method and application thereof. Lithium salt, nickel salt, cobalt salt and manganese salt are dissolved in a uniform medium, a double chelating agent is wetted, ammonia water is added, the double chelating agent solution is added to the inorganic salt uniform medium, stirred and heated to form a dry gel; ground into powder, calcined to obtain a ternary material; tetraethyl orthosilicate, ethanol and surfactant hexadecyltrimethylammonium bromide are added to the ternary nano material aqueous solution, precipitated by centrifugation, washed, dried and calcined to obtain a silica-ternary core-shell positive electrode material; silver oxide is dissolved in water to form solution A; PVP is dissolved in water to form solution B; solution B is added dropwise to solution A to obtain solution C; the silica-ternary core-shell positive electrode material is added to solution C to obtain solution D; a reducing agent is added dropwise to solution D, and the final product is obtained after washing, suction filtration and drying. However, the silver-loaded mesoporous silica-coated ternary positive electrode material uses silicon oxide to coat the ternary positive electrode material. Since the capacity of silicon oxide is relatively low, the capacity of the silver-loaded mesoporous silica-coated ternary positive electrode material is limited and cannot meet the needs in practical applications.
[0005] CN117810404A discloses a modified nickel-cobalt-aluminum ternary positive electrode material and its preparation method and application. The preparation method of the modified nickel-cobalt-aluminum ternary positive electrode material provided in the document comprises the following steps: 1) mixing a nickel-cobalt precursor, a lithium source, an aluminum source and SiO2, and heat-treating them in an oxygen atmosphere to obtain a silicon dioxide-doped ternary positive electrode material; 2) the silicon dioxide-doped ternary positive electrode material obtained in step 1) is soaked in a hydrofluoric acid solution, stirred, washed, dried, and then mixed with an ionic liquid and sintered to obtain the modified nickel-cobalt-aluminum ternary positive electrode material. However, the modified nickel-cobalt-aluminum ternary positive electrode material uses SiO2 to dope the ternary positive electrode material, which cannot solve the problem of side reactions in the ternary positive electrode material, resulting in a faster energy decay rate.
[0006] The coated modified ternary cathode materials disclosed in the prior art all have certain defects, and there is a problem that it is impossible to effectively suppress the side reactions of high-nickel ternary cathode materials while improving the lithium ion capacity and rate performance of high-nickel ternary cathode materials. Therefore, it is very important to develop and design a new type of coated modified ternary cathode material and its preparation method and application. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a coated modified ternary positive electrode material and a preparation method and application thereof. The present invention provides a coated modified ternary positive electrode material, wherein the surface of the ternary positive electrode material core in the coated modified ternary positive electrode material is sequentially coated with a silicon oxide layer, a transition layer and a carbon layer with uniform composition, and the three coating layers effectively prevent the interaction between the ternary positive electrode material core and the electrolyte, reduce side reactions, and thus improve the cycle stability of the battery prepared with the coated modified ternary positive electrode material; in addition, the silicon oxide in the silicon oxide layer and the transition layer provides a higher lithium ion capacity, thereby improving the lithium ion capacity of the coated modified ternary positive electrode material; in addition, the carbon layer has good electronic conductivity, thereby improving the electronic conductivity of the coated modified ternary positive electrode material, thereby improving the rate performance.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In the first aspect, the present invention provides a coated modified ternary positive electrode material, which comprises a ternary positive electrode material core, and a silicon oxide layer, a transition layer and a carbon layer sequentially coated on the surface of the ternary positive electrode material core; the transition layer is composed of silicon oxide and carbon.
[0010] The present invention provides a coated modified ternary positive electrode material, wherein the surface of the ternary positive electrode material core in the coated modified ternary positive electrode material is coated with a silicon oxide layer, a transition layer and a carbon layer with uniform composition in sequence, and the three coating layers effectively prevent the interaction between the ternary positive electrode material core and the electrolyte, reduce side reactions, and thus improve the cycle stability of a battery prepared with the coated modified ternary positive electrode material; in addition, the silicon oxide in the silicon oxide layer and the transition layer provides a higher lithium ion capacity, thereby improving the lithium ion capacity of the coated modified ternary positive electrode material; in addition, the carbon layer has good electron transmission capability, thereby improving the electronic conductivity of the coated modified ternary positive electrode material, thereby improving the rate performance.
[0011] Preferably, the D50 particle size of the ternary positive electrode material core is 2 to 15 μm, for example, it can be 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm or 15 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] Preferably, the thickness of the silicon monoxide layer is 1 to 5 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] Preferably, the thickness of the transition layer is 0.1-0.2 μm, for example, it can be 0.11 μm, 0.12 μm, 0.13 μm, 0.14 μm, 0.15 μm, 0.16 μm, 0.17 μm, 0.18 μm, 0.19 μm or 0.2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the thickness of the carbon layer is 0.1-0.5 μm, for example, it can be 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm or 0.5 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In a second aspect, the present invention provides a method for preparing the coated modified ternary positive electrode material according to the first aspect, the preparation method comprising:
[0016] (1) mixing a metal mixed salt solution, a precipitant solution and a complexing agent solution to perform a coprecipitation reaction to obtain a mixed solution containing a ternary positive electrode material core;
[0017] (2) after adjusting the pH of the mixed solution obtained in step (1), a silicic acid solution and a precipitant solution are simultaneously added to perform silicate coating to obtain a silicate-coated ternary cathode material core;
[0018] (3) The silicate-coated ternary cathode material core obtained in step (2) is mixed with an organic solution, and then calcined in a protective atmosphere to obtain the coated modified ternary cathode material.
[0019] The methods for coating the core of the ternary positive electrode material in the prior art often fail to obtain a coating layer with uniform composition, and it is difficult to control the thickness of the coating layer. Uneven coating will cause the protective effect of the coating layer to fail during the cycle, and excessive coating thickness will affect the ion and electron transmission of the core of the ternary positive electrode material. Moreover, the prior art mostly uses mixed material calcination coating and high-temperature calcination, which will cause nickel-lithium mixing and cause changes in the material structure, thereby causing irreversible loss of capacity.
[0020] In the preparation method of the coated modified ternary positive electrode material provided by the present invention, after the ternary precursor is prepared by the co-precipitation method, silicic acid is directly added so that the silicate is uniformly coated on the surface of the ternary positive electrode material core, and a uniform silicon oxide layer is generated during the subsequent calcination process, and the thickness of the silicon oxide layer can be controlled by adjusting the amount of silicate solution added and the silicate coating time; in addition, in the preparation method, the micro-viscosity of the organic solution is utilized to coat the organic matter on the surface of the material, and the organic matter is subsequently carbonized into a carbon protective layer when calcined in a protective atmosphere, and a transition layer with a uniform composition of silicon oxide and carbon is formed between the carbon protective layer and the silicon oxide layer.
[0021] Preferably, the metal mixed salt solution in step (1) includes Ni salt, Co salt and Mn salt. Taking the total molar amount of metal ions in the metal mixed salt solution as percentage, the molar fraction of Ni ions in the metal mixed salt solution is not less than 80%, for example, it can be 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94% or 96%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the total concentration of metal ions in the metal mixed salt solution in step (1) is 1.5 to 2 mol / L, for example, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, the Ni salt, Co salt and Mn salt each independently include any one of sulfate, nitrate or chloride or a combination of at least two thereof, and typical but non-limiting combinations include a combination of sulfate and nitrate, a combination of nitrate and chloride, or a combination of sulfate, nitrate and chloride.
[0024] Preferably, the precipitant solution in step (1) comprises sodium hydroxide solution and / or potassium hydroxide solution.
[0025] Preferably, the concentration of the precipitant solution in step (1) is 5 to 10 mol / L, for example, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the complexing agent solution in step (1) comprises aqueous ammonia and / or oxalic acid solution.
[0027] Preferably, the concentration of the complexing agent solution in step (1) is 5 to 20 mol / L, for example, 5 mol / L, 7 mol / L, 9 mol / L, 10 mol / L, 12 mol / L, 14 mol / L, 16 mol / L, 18 mol / L or 20 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the temperature during the coprecipitation reaction in step (1) is 50-80°C, for example, it can be 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the coprecipitation reaction in step (1) is also accompanied by stirring at a speed of 200 to 700 rpm, for example, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm or 700 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, the pH of the coprecipitation reaction in step (1) is 9 to 12, for example, 9, 9.5, 10, 10.5, 11, 11.5 or 12, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Preferably, the D50 particle size of the ternary positive electrode material core in step (1) is 2 to 15 μm, for example, it can be 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm or 15 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the adjustment in step (2) includes adjusting the pH of the mixed solution obtained in step (1) to 9-10, for example, it can be 9, 9.2, 9.4, 9.6, 9.8 or 10, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; the adjustment method includes adding a precipitant solution and a complexing agent solution.
[0033] Preferably, the concentration of the silicic acid solution in step (2) is 0.05-0.1 mol / L, for example, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the temperature during silicate coating in step (2) is 40-60°C, for example, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the silicate coating in step (2) is also accompanied by stirring at a rotation speed of 100 to 200 rpm, for example, it can be 100 rpm, 110 rpm, 120 rpm, 130 rpm, 140 rpm, 150 rpm, 160 rpm, 170 rpm, 180 rpm, 190 rpm or 200 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the pH of the silicate coating in step (2) is 9 to 10, for example, 9, 9.2, 9.4, 9.6, 9.8 or 10, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, after the silicate coating in step (2), the process further includes sequentially performing a first solid-liquid separation and a first drying to obtain a silicate-coated ternary positive electrode material core.
[0038] Preferably, the first solid-liquid separation method includes centrifugation.
[0039] Preferably, the first drying temperature is 80-110°C, for example, it can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the organic solution in step (3) comprises a polyvinyl alcohol aqueous solution with a concentration of 10 to 30 g / L, for example, 10 g / L, 12 g / L, 14 g / L, 16 g / L, 18 g / L, 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L or 30 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the mixing temperature in step (3) is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the mixing in step (3) is accompanied by stirring at a speed of 80 to 120 rpm, for example, 80 rpm, 85 rpm, 90 rpm, 95 rpm, 100 rpm, 105 rpm, 110 rpm, 115 rpm or 120 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] Preferably, step (3) further includes a second solid-liquid separation and a second drying performed sequentially between the mixing and calcining.
[0044] Preferably, the second drying temperature is 60-100°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the second solid-liquid separation method includes centrifugation.
[0046] Preferably, the protective atmosphere in step (3) comprises nitrogen and / or an inert gas.
[0047] Preferably, the calcination temperature in step (3) is 400-600° C. and the calcination time is 2-8 hours.
[0048] The calcination temperature in step (3) of the present invention is 400-600°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C or 600°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:
[0050] (1) mixing a metal mixed salt solution with a total metal ion concentration of 1.5 to 2 mol / L, a precipitant solution with a concentration of 5 to 10 mol / L, and a complexing agent solution with a concentration of 5 to 20 mol / L, controlling the temperature to 50 to 80° C., the stirring speed to 200 to 700 rpm, and the pH to 9 to 12, and performing a coprecipitation reaction to obtain a mixed solution containing a ternary cathode material core with a D50 particle size of 2 to 15 μm;
[0051] (2) adjusting the pH of the mixed solution obtained in step (1) to 9-10 by adding a precipitant solution and a complexing agent solution, then simultaneously adding a silicic acid solution with a concentration of 0.05-0.1 mol / L and a precipitant solution with a concentration of 5-10 mol / L, controlling the temperature to 40-60° C., the stirring speed to 100-200 rpm, and the pH to 9-10, performing silicate coating, and then centrifuging and drying the obtained solid at 80-110° C. to obtain a silicate-coated ternary positive electrode material core;
[0052] (3) Controlling the temperature to 60-80°C and the stirring speed to 80-120 rpm, mixing the silicate-coated ternary cathode material core obtained in step (2) with a polyvinyl alcohol aqueous solution having a concentration of 10-30 g / L, centrifuging and drying at 60-100°C, and then calcining at 400-600°C for 2-8 h in nitrogen and / or inert gas to obtain the coated modified ternary cathode material.
[0053] In a third aspect, the present invention provides a positive electrode sheet, which includes the coated modified ternary positive electrode material described in the first aspect.
[0054] In a fourth aspect, the present invention provides a lithium battery, comprising the positive electrode sheet described in the third aspect.
[0055] A fifth aspect is an electric device, comprising the lithium battery described in the fourth aspect.
[0056] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) The present invention provides a coated modified ternary positive electrode material, wherein the surface of the ternary positive electrode material core in the coated modified ternary positive electrode material is coated with a silicon oxide layer, a transition layer and a carbon layer with uniform composition in sequence, and the three coating layers effectively prevent the interaction between the ternary positive electrode material core and the electrolyte, reduce side reactions, and thus improve the cycle stability of the battery prepared with the coated modified ternary positive electrode material; in addition, the silicon oxide in the silicon oxide layer and the transition layer provides a higher lithium ion capacity, thereby improving the lithium ion capacity of the coated modified ternary positive electrode material; in addition, the carbon layer has good electronic conductivity, thereby improving the electronic conductivity of the coated modified ternary positive electrode material, thereby improving the rate performance;
[0059] (2) In the preparation method of the coated modified ternary positive electrode material provided by the present invention, after the ternary precursor is prepared by the co-precipitation method, silicic acid is directly added so that the silicate is uniformly coated on the surface of the ternary positive electrode material core, and a uniform silicon oxide layer is generated during the subsequent calcination process, and the thickness of the silicon oxide layer can be controlled by adjusting the amount of silicate solution added and the silicate coating time; in addition, in the preparation method, the micro-viscosity of the organic solution is utilized to coat the organic matter on the surface of the material, and the organic matter is subsequently carbonized into a carbon protective layer when calcined in a protective atmosphere, and a transition layer with a uniform composition of silicon oxide and carbon is formed between the carbon protective layer and the silicon oxide layer. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0061] Example 1
[0062] The present embodiment provides a coated modified ternary positive electrode material, which includes a ternary positive electrode material core with a D50 particle size of 8μm, and a silicon oxide layer with a thickness of 3μm, a transition layer with a thickness of 0.15μm and a carbon layer with a thickness of 0.3μm coated on the surface of the ternary positive electrode material core in sequence; the transition layer is composed of silicon oxide and carbon.
[0063] The preparation method of the coated modified ternary positive electrode material comprises:
[0064] (1) a metal mixed salt solution with a total metal ion concentration of 1.8 mol / L (a molar ratio of Ni salt, Co salt and Mn salt of 8:1:1), a sodium hydroxide solution with a concentration of 8 mol / L and an ammonia solution with a concentration of 12 mol / L were mixed, the temperature was controlled at 50° C., the stirring speed was 200 rpm, and the pH was 9, and a coprecipitation reaction was performed to obtain a mixed solution containing a ternary cathode material core with a D50 particle size of 8 μm;
[0065] (2) After adjusting the pH of the mixed solution obtained in step (1) to 9.5 by adding sodium hydroxide solution and ammonia water, a 0.05 mol / L silicic acid solution and an 8 mol / L sodium hydroxide solution were simultaneously added, the temperature was controlled at 50° C., the stirring speed was 150 rpm, and the pH was 9.5, and silicate coating was performed, and then the obtained solid was dried at 80° C. after centrifugation to obtain a silicate-coated ternary positive electrode material core;
[0066] (3) Controlling the temperature to 70°C and the stirring speed to 100 rpm, mixing the silicate-coated ternary positive electrode material core obtained in step (2) with a polyvinyl alcohol aqueous solution having a concentration of 10 g / L, centrifuging and drying at 80°C, and then calcining at 400°C for 2 h in an argon atmosphere to obtain the coated modified ternary positive electrode material.
[0067] Example 2
[0068] The present embodiment provides a coated modified ternary positive electrode material, which includes a ternary positive electrode material core with a D50 particle size of 12 μm, and a silicon oxide layer with a thickness of 2 μm, a transition layer with a thickness of 1.8 μm and a carbon layer with a thickness of 0.4 μm coated on the surface of the ternary positive electrode material core in sequence; the transition layer is composed of silicon oxide and carbon.
[0069] The preparation method of the coated modified ternary positive electrode material comprises:
[0070] (1) a metal mixed salt solution with a total metal ion concentration of 1.9 mol / L (a molar ratio of Ni salt, Co salt and Mn salt of 8.2:1:0.8), a sodium hydroxide solution with a concentration of 8 mol / L and an ammonia solution with a concentration of 8 mol / L were mixed, the temperature was controlled at 60° C., the stirring speed was 600 rpm, and the pH was 11, and a coprecipitation reaction was performed to obtain a mixed solution containing a ternary cathode material core with a D50 particle size of 12 μm;
[0071] (2) adjusting the pH of the mixed solution obtained in step (1) to 9.8 by adding sodium hydroxide solution and ammonia water, and then simultaneously adding 0.08 mol / L silicic acid solution and 6 mol / L sodium hydroxide solution, controlling the temperature to 45° C., the stirring speed to 180 rpm, and the pH to 9.8, to perform silicate coating, and then centrifuging and drying the obtained solid at 100° C. to obtain a silicate-coated ternary positive electrode material core;
[0072] (3) Controlling the temperature to 65°C and the stirring speed to 110 rpm, mixing the silicate-coated ternary positive electrode material core obtained in step (2) with a polyvinyl alcohol aqueous solution having a concentration of 25 g / L, centrifuging and drying at 90°C, and then calcining at 450°C for 7 h in nitrogen and / or inert gas to obtain the coated modified ternary positive electrode material.
[0073] Example 3
[0074] The present embodiment provides a coated modified ternary positive electrode material, which includes a ternary positive electrode material core with a D50 particle size of 2 μm, and a silicon oxide layer with a thickness of 1 μm, a transition layer with a thickness of 2 μm, and a carbon layer with a thickness of 0.5 μm coated in sequence on the surface of the ternary positive electrode material core; the transition layer is composed of silicon oxide and carbon.
[0075] The preparation method of the coated modified ternary positive electrode material comprises:
[0076] (1) a metal mixed salt solution with a total metal ion concentration of 1.5 mol / L (the molar ratio of Ni salt, Co salt and Mn salt is 8.2:0.8:1), a sodium hydroxide solution with a concentration of 5 mol / L and an ammonia solution with a concentration of 5 mol / L were mixed, the temperature was controlled at 50° C., the stirring speed was 700 rpm, and the pH was 9, and a coprecipitation reaction was performed to obtain a mixed solution containing a ternary cathode material core with a D50 particle size of 2 μm;
[0077] (2) adjusting the pH of the mixed solution obtained in step (1) to 9 by adding sodium hydroxide solution and ammonia water, and then simultaneously adding 0.05 mol / L silicic acid solution and 5 mol / L sodium hydroxide solution, controlling the temperature to 60° C., the stirring speed to 100 rpm, and the pH to 9, to perform silicate coating, and then centrifuging and drying the obtained solid at 110° C. to obtain a silicate-coated ternary positive electrode material core;
[0078] (3) Controlling the temperature at 60°C and the stirring speed at 120 rpm, mixing the silicate-coated ternary positive electrode material core obtained in step (2) with a polyvinyl alcohol aqueous solution with a concentration of 30 g / L, centrifuging and drying at 60°C, and then calcining at 400°C for 8 h in nitrogen and / or inert gas to obtain the coated modified ternary positive electrode material.
[0079] Example 4
[0080] The present embodiment provides a coated modified ternary positive electrode material, which includes a ternary positive electrode material core with a D50 particle size of 15 μm, and a silicon oxide layer with a thickness of 1 μm, a transition layer with a thickness of 0.1 μm and a carbon layer with a thickness of 0.1 μm coated on the surface of the ternary positive electrode material core in sequence; the transition layer is composed of silicon oxide and carbon.
[0081] The preparation method of the coated modified ternary positive electrode material comprises:
[0082] (1) a metal mixed salt solution with a total metal ion concentration of 2 mol / L (a molar ratio of Ni salt, Co salt and Mn salt of 8.3:0.8:0.9), a sodium hydroxide solution with a concentration of 10 mol / L and an ammonia solution with a concentration of 20 mol / L were mixed, the temperature was controlled at 80°C, the stirring speed was 200 rpm, and the pH was 12, and a coprecipitation reaction was performed to obtain a mixed solution containing a ternary cathode material core with a D50 particle size of 15 μm;
[0083] (2) adjusting the pH of the mixed solution obtained in step (1) to 10 by adding sodium hydroxide solution and ammonia water, and then simultaneously adding 0.1 mol / L silicic acid solution and 10 mol / L sodium hydroxide solution, controlling the temperature to 40° C., the stirring speed to 200 rpm, and the pH to 10, to perform silicate coating, and then centrifuging and drying the obtained solid at 80° C. to obtain a silicate-coated ternary positive electrode material core;
[0084] (3) Controlling the temperature at 80°C and the stirring speed at 80 rpm, mixing the silicate-coated ternary positive electrode material core obtained in step (2) with a polyvinyl alcohol aqueous solution with a concentration of 10 g / L, centrifuging and drying at 100°C, and then calcining at 600°C for 2 h in nitrogen and / or inert gas to obtain the coated modified ternary positive electrode material.
[0085] Example 5
[0086] This embodiment provides a coated modified ternary positive electrode material, which is the same as that of Embodiment 1 except that the D50 particle size of the ternary positive electrode material core is 1 μm.
[0087] Example 6
[0088] This embodiment provides a coated modified ternary positive electrode material, which is the same as that of Embodiment 1 except that the D50 particle size of the ternary positive electrode material core is 20 μm.
[0089] Example 7
[0090] This embodiment provides a coated modified ternary positive electrode material, which is the same as Example 1 except that in step (2) of the method for preparing the coated modified ternary positive electrode material, the pH of the mixed solution obtained in step (1) is adjusted to 8, and the pH during silicate coating is controlled to 8.
[0091] Example 8
[0092] This embodiment provides a coated modified ternary positive electrode material, which is the same as Embodiment 1 except that in step (2) of the method for preparing the coated modified ternary positive electrode material, the pH of the mixed solution obtained in step (1) is adjusted to 11.
[0093] Example 9
[0094] This embodiment provides a coated modified ternary positive electrode material, which is the same as Embodiment 1 except that the concentration of the silicate solution in step (2) of the preparation method of the coated modified ternary positive electrode material is 0.02 mol / L.
[0095] Example 10
[0096] This embodiment provides a coated modified ternary positive electrode material, which is the same as Embodiment 1 except that the concentration of the silicic acid solution in step (2) of the preparation method of the coated modified ternary positive electrode material is 0.15 mol / L.
[0097] Embodiment 11
[0098] This embodiment provides a coated modified ternary positive electrode material, which is the same as Embodiment 1 except that the concentration of the polyvinyl alcohol aqueous solution in step (3) of the preparation method of the coated modified ternary positive electrode material is 5 g / L.
[0099] Example 12
[0100] This embodiment provides a coated modified ternary positive electrode material, which is the same as Embodiment 1 except that the concentration of the polyvinyl alcohol aqueous solution in step (3) of the preparation method of the coated modified ternary positive electrode material is 40 g / L.
[0101] Embodiment 13
[0102] This embodiment provides a coated modified ternary positive electrode material, which is the same as Embodiment 1 except that the calcination temperature in step (3) of the preparation method of the coated modified ternary positive electrode material is 300°C.
[0103] Embodiment 14
[0104] This embodiment provides a coated modified ternary positive electrode material, which is the same as Embodiment 1 except that the calcination temperature in step (3) of the preparation method of the coated modified ternary positive electrode material is 800°C.
[0105] Comparative Example 1
[0106] This comparative example provides a coated modified ternary positive electrode material, wherein the coated modified ternary positive electrode material comprises a ternary positive electrode material core having a D50 particle size of 8 μm, and a silicon oxide layer having a thickness of 3 μm coated on the surface of the ternary positive electrode material core;
[0107] The preparation method of the coated modified ternary positive electrode material is:
[0108] (1) a metal mixed salt solution with a total metal ion concentration of 1.8 mol / L (a molar ratio of Ni salt, Co salt and Mn salt of 8:1:1), a sodium hydroxide solution with a concentration of 8 mol / L and an ammonia solution with a concentration of 12 mol / L were mixed, the temperature was controlled at 50° C., the stirring speed was 200 rpm, and the pH was 9, and a coprecipitation reaction was performed to obtain a mixed solution containing a ternary cathode material core with a D50 particle size of 8 μm;
[0109] (2) After adjusting the pH of the mixed solution obtained in step (1) to 9.5 by adding a precipitant and a complexing agent, a 0.05 mol / L silicic acid solution and an 8 mol / L sodium hydroxide solution are simultaneously added, the temperature is controlled to 50° C., the stirring speed is 150 rpm, and the pH is 9.5, and silicate coating is performed, and then the obtained solid is dried at 80° C. after centrifugation to obtain a silicate-coated ternary positive electrode material core;
[0110] (3) The silicate-coated ternary cathode material core obtained in step (2) is calcined at 400° C. for 2 h in an argon atmosphere to obtain the coated modified ternary cathode material.
[0111] Comparative Example 2
[0112] This comparative example provides a coated modified ternary positive electrode material, wherein the coated modified ternary positive electrode material comprises a ternary positive electrode material core with a D50 particle size of 8 μm, and a carbon layer with a thickness of 0.3 μm coated on the surface of the ternary positive electrode material core;
[0113] The preparation method of the coated modified ternary positive electrode material is:
[0114] (1) A metal mixed salt solution with a total metal ion concentration of 1.8 mol / L (the molar ratio of Ni salt, Co salt and Mn salt is 8:1:1), a sodium hydroxide solution with a concentration of 8 mol / L and an ammonia solution with a concentration of 12 mol / L were mixed, the temperature was controlled at 50° C., the stirring speed was 200 rpm, and the pH was 9, and a coprecipitation reaction was performed to obtain a mixed solution of a ternary cathode material core, which was then centrifuged and dried at 80° C. to obtain a ternary cathode material core with a D50 particle size of 8 μm;
[0115] (2) The temperature was controlled at 70°C and the stirring speed was 100 rpm. The ternary cathode material core obtained in step (1) was mixed with a polyvinyl alcohol aqueous solution having a concentration of 10 g / L, and then centrifuged and dried at 80°C. The mixture was then calcined at 400°C for 2 h in an argon atmosphere to obtain the coated modified ternary cathode material.
[0116] The lithium-ion battery is prepared by using the coated modified ternary positive electrode material provided in the above embodiment and comparative example: the obtained coated modified ternary positive electrode material, conductive carbon black SP (TIMCAL) and polyvinylidene fluoride PVDF (HSV900) are mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone is used as a solvent, and the mixture is mixed and stirred into a slurry, and the obtained slurry is evenly coated on an aluminum foil with a scraper with a coating gap of 100 μm; after coating, it is first blown and dried, and then rolled and cut into circular electrode sheets, and then vacuum dried at 120° C. and the weight of the electrode sheets is weighed to obtain a button half-cell positive electrode sheet; a metal lithium sheet is selected as the negative electrode, a PP microporous membrane is selected as the diaphragm, and a lithium battery basic electrolyte is selected as the electrolyte, and the positive electrode sheet, the metal lithium sheet, the diaphragm and the electrolyte are assembled to obtain a button battery;
[0117] First, the button cell was activated three times at 0.1C rate / 2.7-4.3V, and then the electrochemical performance of the activated button cell was tested at 2.7-4.3V, 0.1C / 0.5C to obtain the discharge capacity and the capacity retention rate after 100 cycles, as shown in Table 1.
[0118] Table 1
[0119]
[0120]
[0121] From Table 1, we can get:
[0122] (1) The lithium-ion battery prepared by using the coated modified ternary cathode material provided in Examples 1 to 4 of the present invention exhibits a high initial discharge capacity, excellent rate performance and strong cycle stability;
[0123] (2) By comparing Example 1 with Examples 5 and 6, it can be seen that the D50 particle size of the ternary cathode material core of the present invention affects the performance of the lithium-ion battery; when the D50 particle size of the ternary cathode material core is 2 to 15 μm, the lithium-ion battery has better performance. This is because the particle size is too small and the material tap density is low, resulting in a lower energy density; when the particle size is too large, the transmission path of lithium ions becomes longer, resulting in poor rate performance;
[0124] (3) By comparing Example 1 with Examples 7 and 8, it can be seen that in step (2) of the method for preparing the coated modified ternary positive electrode material of the present invention, adjusting the pH of the mixed solution to 9-10, and controlling the pH during silicate coating to 9-10, is conducive to obtaining a coated modified ternary positive electrode material with better performance and a lithium battery with better performance. This is because within this pH range, the silicon material tends to be slowly and evenly coated on the surface of the ternary material core. If the pH is too high, the silicon material will agglomerate, and if it is too low, an amorphous structure will be generated, and effective coating cannot be achieved;
[0125] (4) By comparing Example 1 with Examples 9 and 10, it can be seen that the concentration of the silicate solution in step (2) of the method for preparing the coated modified ternary positive electrode material of the present invention will affect the performance of the lithium-ion battery; when the concentration of the silicate solution is 0.05-0.1 mol / L, it is conducive to obtaining a coated modified ternary positive electrode material with better performance and a lithium battery with better performance, because a silicate solution with too high a concentration will be in a colloidal state and cannot be used for coating; too low a concentration will reduce the coating efficiency;
[0126] (5) By comparing Example 1 with Examples 11 and 12, it can be seen that the concentration of the polyvinyl alcohol aqueous solution in step (3) of the method for preparing the coated modified ternary positive electrode material of the present invention will affect the performance of the lithium ion battery; when the concentration of the polyvinyl alcohol aqueous solution is 10 to 30 g / L, it is conducive to obtaining a coated modified ternary positive electrode material with better performance and a lithium battery with better performance. This is because the polyvinyl alcohol solution has a good viscosity in this concentration range and can adhere to the surface of the material, and decompose into a shell structure that is tightly coated and interpenetrated with the silicon dioxide layer during subsequent calcination;
[0127] (6) By comparing Example 1 with Examples 13 and 14, it can be seen that the calcination temperature in step (3) of the method for preparing the coated modified ternary positive electrode material of the present invention will affect the performance of the lithium-ion battery; when the calcination temperature is 400-600°C, it is conducive to obtaining a coated modified ternary positive electrode material with better performance and a lithium battery with better performance, because this temperature range is conducive to the decomposition of silicate into silicon oxide and the full carbonization of polyvinyl alcohol into a carbon layer protective shell; if the temperature is too low, the shell cannot be fully carbonized, and if the temperature is too high, the shell further decomposes and densifies, which is not conducive to improving the electrical performance of the electrode material;
[0128] (7) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the present invention provides a coated modified ternary positive electrode material, wherein the surface of the ternary positive electrode material core in the coated modified ternary positive electrode material is sequentially coated with a silicon oxide layer, a transition layer and a carbon layer with uniform composition, and the three coating layers effectively prevent the interaction between the ternary positive electrode material core and the electrolyte, reduce side reactions, and thus improve the cycle stability of the battery prepared with the coated modified ternary positive electrode material; in addition, the silicon oxide in the silicon oxide layer and the transition layer provides a higher lithium ion capacity, thereby improving the lithium ion capacity of the coated modified ternary positive electrode material; in addition, the carbon layer has good electronic conductivity, thereby improving the coated modified ternary positive electrode The electronic conductivity of the material is improved, thereby improving the rate performance; in the preparation method of the coated modified ternary positive electrode material provided by the present invention, after the ternary precursor is prepared by the co-precipitation method, silicic acid is directly added to make the silicate uniformly coated on the surface of the ternary positive electrode material core, and a uniform silicon oxide layer is generated during the subsequent calcination process, and the thickness of the silicon oxide layer can be controlled by adjusting the amount of silicate solution added and the silicate coating time; in addition, in the preparation method, the micro-viscosity of the organic solution is utilized to coat the organic matter on the surface of the material, and the organic matter is subsequently carbonized into a carbon protective layer when calcined in a protective atmosphere, and a transition layer with a uniform composition of silicon oxide and carbon is formed between the carbon protective layer and the silicon oxide layer.
[0129] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A coated modified ternary positive electrode material, characterized in that: The coated modified ternary positive electrode material comprises a ternary positive electrode material core, and a silicon oxide layer, a transition layer and a carbon layer sequentially coated on the surface of the ternary positive electrode material core; the transition layer is composed of silicon oxide and carbon.
2. The coated modified ternary positive electrode material according to claim 1, characterized in that: The D50 particle size of the ternary positive electrode material core is 2 to 15 μm; Preferably, the thickness of the silicon oxide layer is 1 to 5 μm; Preferably, the thickness of the transition layer is 0.1 to 2 μm; Preferably, the carbon layer has a thickness of 0.1-0.5 μm.
3. A method for preparing the coated modified ternary positive electrode material according to claim 1 or 2, characterized in that: The preparation method comprises: (1) mixing a metal mixed salt solution, a precipitant solution and a complexing agent solution to perform a coprecipitation reaction to obtain a mixed solution containing a ternary positive electrode material core; (2) after adjusting the pH of the mixed solution obtained in step (1), a silicic acid solution and a precipitant solution are simultaneously added to perform silicate coating to obtain a silicate-coated ternary cathode material core; (3) The silicate-coated ternary cathode material core obtained in step (2) is mixed with an organic solution, and then calcined in a protective atmosphere to obtain the coated modified ternary cathode material.
4. The preparation method according to claim 3, characterized in that: The temperature during the coprecipitation reaction in step (1) is 50-80° C. Preferably, the coprecipitation reaction in step (1) is also accompanied by stirring at a speed of 200 to 700 rpm; Preferably, the pH of the coprecipitation reaction in step (1) is 9 to 12; Preferably, the D50 particle size of the ternary positive electrode material core in step (1) is 2 to 15 μm.
5. The preparation method according to claim 3 or 4, characterized in that: The adjustment in step (2) includes adjusting the pH of the mixed solution obtained in step (1) to 9-10, and the adjustment method includes adding a precipitant solution and a complexing agent solution; Preferably, the concentration of the silicic acid solution in step (2) is 0.05-0.1 mol / L; Preferably, the temperature during the silicate coating in step (2) is 40-60°C; Preferably, the silicate coating in step (2) is accompanied by stirring at a speed of 100 to 200 rpm; Preferably, the pH value during the silicate coating in step (2) is 9-10.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The organic solution in step (3) comprises a polyvinyl alcohol aqueous solution with a concentration of 10 to 30 g / L; Preferably, the temperature during the mixing in step (3) is 60 to 80°C; Preferably, the mixing in step (3) is accompanied by stirring at a speed of 80 to 120 rpm; Preferably, the calcination temperature in step (3) is 400-600° C. and the calcination time is 2-8 hours.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The preparation method comprises: (1) mixing a metal mixed salt solution with a total metal ion concentration of 1.5 to 2 mol / L, a precipitant solution with a concentration of 5 to 10 mol / L, and a complexing agent solution with a concentration of 5 to 20 mol / L, controlling the temperature to 50 to 80° C., the stirring speed to 200 to 700 rpm, and the pH to 9 to 12, and performing a coprecipitation reaction to obtain a mixed solution containing a ternary cathode material core with a D50 particle size of 2 to 15 μm; (2) adjusting the pH of the mixed solution obtained in step (1) to 9-10 by adding a precipitant solution and a complexing agent solution, then simultaneously adding a silicic acid solution with a concentration of 0.05-0.1 mol / L and a precipitant solution with a concentration of 5-10 mol / L, controlling the temperature to 40-60° C., the stirring speed to 100-200 rpm, and the pH to 9-10, performing silicate coating, and then centrifuging and drying the obtained solid at 80-110° C. to obtain a silicate-coated ternary positive electrode material core; (3) Controlling the temperature to 60-80°C and the stirring speed to 80-120 rpm, mixing the silicate-coated ternary cathode material core obtained in step (2) with a polyvinyl alcohol aqueous solution having a concentration of 10-30 g / L, centrifuging and drying at 60-100°C, and then calcining at 400-600°C for 2-8 h in nitrogen and / or inert gas to obtain the coated modified ternary cathode material.
8. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the coated modified ternary positive electrode material according to claim 1 or 2.
9. A lithium battery, characterized in that: The lithium battery comprises the positive electrode sheet according to claim 8.
10. An electric device, characterized in that: The electric device comprises the lithium battery according to claim 9.
Citation Information
Patent Citations
Silver loaded mesoporous silicon oxide coated ternary cathode material, and preparation method and applications thereof
CN106571455A
Modified nickel-cobalt-aluminum ternary positive electrode material and preparation method and application thereof
CN117810404A
Cited By
Neodymium-copper-modified high-nickel ternary positive electrode material as well as preparation method and application thereof
CN120581583A